Role of the Ang2-Tie2 axis in vascular damage driven by high glucose or nucleoside diphosphate kinase B deficiency - Chatterjee, Anupriya; Eshwaran, Rachana; Huang, Hongpeng; Zhao, Di; Schmidt, Martina; Wieland, Thomas; Feng, Yuxi (International journal of molecular sciences, 2020)
Ablation of nucleoside diphosphate kinase B (NDPK-B) in mice causes a breakdown of the neurovascular unit in the retina, mimicking diabetic retinopathy. The NDPK-B deficiency-induced vascular damage is mediated by excessive angiopoietin 2 (Ang2). Herein, the potential involvement of its receptor, Tie2, was investigated. NDPK-B-deficient mouse retinas showed an upregulation of Tie2, specifically in the deep capillary layer. A similar upregulation of Tie2 was observed in cultured endothelial cells (ECs) from different origins upon NDPK-B depletion, whereas high glucose (HG) treatment did not alter Tie2 expression. Immunofluorescence staining and subcellular fractionation showed that the majority of Tie2 upregulation occurred at the plasma membrane. Similar to HG, however, NDPK-B depletion reduced Tie2 tyrosine phosphorylation. Compared to HG, a stronger increase of Ang2 was observed in NDPK-B depleted ECs. Treatment of ECs with soluble Tie2 or siRNA-mediated Tie2 knockdown attenuated NDPK-B depletion- but not HG-induced Ang2 upregulation. Like NDPK-B depletion, overexpression of recombinant Ang2 in ECs enhanced Ang2 secretion and concomitantly promoted the upregulation of Tie2. Thus, we identified a new mechanism showing that after reaching a threshold level of secretion, Ang2 sustains its own expression and secretion by a Tie2-dependent positive feedback loop.